Dynamic analysis of laminated composite thermo-magneto-electro-elastic shells - Albarody, T.M.B. (Korean Society of Mechanical Engineers, 2014)
Modeling of piezo-laminated shell structure and/or shell embedded smart lamina influenced by thermo-magneto-electro-elastic load presents a challenge to be formulated and solved. We derived an analytical model based on the first-order transversally shear deformation theory with involvement of Codazzi-Gauss geometrical discretion. The present invented model and the desired boundary conditions were rigorouslyderived using Hamiltonâs principle with cooperationof Gibbs free energy functions. The model was castin theversion of a general laminated composite shell of revolution, in order to be simplified to account for most occurring shell geometries, and intended for wide range of smart materials. To ensure a conventional effective medium model, a rectangular plane shell of zero and large curvatures wasselected for analysis to justify the model. Hence, the generic forced-solution procedures for the response were derived, and its natural frequencies were evaluated in a simply supported boundary condition. Investigatedexamples areaccompanied and noteworthy conclusions drawn which highlight the issues of the implementation of the exact solution, implication of the effects of the material properties, lay-ups of the constituent layers, and shell parameters on the free vibrational behavior. Â© 2014, The Korean Society of Mechanical Engineers and Springer-Verlag Berlin Heidelberg.